2007
DOI: 10.1007/s10453-007-9076-9
|View full text |Cite
|
Sign up to set email alerts
|

Detailed identification of desert-originated bacteria carried by Asian dust storms to Japan

Abstract: Several halotolerant bacteria were isolated from dust allowed to settle passively on saline medium in Higashi-Hiroshima, Japan during Asia dust events in [2005][2006]. The primary identification, based on the sequence similarity of the 16S rRNA gene, revealed that these isolates were strains of Bacillus subtilis, B. licheniformis, Staphylococcus epidermidis, Gracillibacillus sp., and Halomonas venusta. A parallel investigation carried out on desert sand collected directly from sand dunes in Dunhuang, Gobi Dese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 40 publications
3
48
0
Order By: Relevance
“…Echigo et al reported that similar members of halobacteria inhabit non-saline environments in an area surrounding Tokyo, Japan, and indicated that they may have been introduced by KOSA events (Echigo et al 2005). Some halobacterial species that were found in both the Gobi Desert and the atmospheric dust impacting Japan had similar genetic identities, thereby supporting the hypothesis of KOSA transport and deposition (Hua et al 2007). The results of this investigation suggest that, at high attitudes, the extreme halophilic bacteria would maintain their viabilities and be tolerant to the strict environmental stresses of atmosphere.…”
Section: Discussionsupporting
confidence: 54%
“…Echigo et al reported that similar members of halobacteria inhabit non-saline environments in an area surrounding Tokyo, Japan, and indicated that they may have been introduced by KOSA events (Echigo et al 2005). Some halobacterial species that were found in both the Gobi Desert and the atmospheric dust impacting Japan had similar genetic identities, thereby supporting the hypothesis of KOSA transport and deposition (Hua et al 2007). The results of this investigation suggest that, at high attitudes, the extreme halophilic bacteria would maintain their viabilities and be tolerant to the strict environmental stresses of atmosphere.…”
Section: Discussionsupporting
confidence: 54%
“…The isolations of Bacillus species were also predominantly obtained from dust samples collected in downwind areas (Hua et al, 2007;Gorbushina et al, 2007). Members of the genus Bacillus are reported to form resistant endospores that support their survival in the atmosphere (Nicholson et al, 2000).…”
Section: Bacterial Populations Associated With Dust Eventsmentioning
confidence: 99%
“…Tateyama accumulating aerosols with snow fall during the winter and spring seasons, the snow layer that included Kosa mineral particles contained halotolerant bacteria identified as the B. subtilis group but layers without dust particles did not contain B. subtilis (Maki et al 2011). Species related to B. subtilis were isolated from sand samples of the Gobi Desert area (Hua et al 2007) and reported to dominate in the surface air of Saul City during Kosa events (Jeon et al 2011). Therefore, B. subtilis in the air sample was possibly transported with dust mineral particles from the continental desert area.…”
Section: Discussionmentioning
confidence: 99%
“…Halotolerant bacteria are known to tolerant to these environmental stressors as well as high salinity (Russell 1989), and to be typical of bioaerosols that are transported across hundreds to thousands of kilometers (Yukimura et al 2009). Some halotolerant bacteria isolated from sand dunes in the Gobi Desert were belonging to the genus Bacillus, which includes species such as B. subtilis and identical to bacterial species isolated in Higashi-Hiroshima, Japan, indicating the possibility of their long-range transport (Hua et al, 2007). An experimental design facilitating halotolerant bacterial activities in bioaerosol samples is expected to be useful for analyzing the atmospheric microorganisms.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation